2022
DOI: 10.1002/anie.202200190
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Level Insights into the Notorious CO Poisoning of Platinum Catalyst

Abstract: Carbon monoxide (CO) is notorious for its strong adsorption to poison platinum group metal catalysts in the chemical industry. Here, we conceptually distinguish and quantify the effects of the occupancy and energy of d electrons, emerging as the two vital factors in d-band theory, for CO poisoning of Pt nanocatalysts. The stepwise defunctionalization of carbon support is adopted to fine-tune the 5d electronic structure of supported Pt nanoparticles. Excluding other promotional mechanisms, the increase of Pt 5d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Due to the doping of oxalic acid, the O-atom content was increased after the modification. BET trial showed (shown in Figure 2) that calcination increased the specific surface area (276.12 m 2 /g) relative to SAA (191.09 m 2 /g), while C (X °C) -SAA had a larger specific surface area, which was favorable for F − to have sufficient adsorption site (Zhang et al, 2022b). Meanwhile, the specific surface of C-SAAoa was increased to 335.38 m 2 /g.…”
Section: Effect Of Calcination Temperature and Oxalic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the doping of oxalic acid, the O-atom content was increased after the modification. BET trial showed (shown in Figure 2) that calcination increased the specific surface area (276.12 m 2 /g) relative to SAA (191.09 m 2 /g), while C (X °C) -SAA had a larger specific surface area, which was favorable for F − to have sufficient adsorption site (Zhang et al, 2022b). Meanwhile, the specific surface of C-SAAoa was increased to 335.38 m 2 /g.…”
Section: Effect Of Calcination Temperature and Oxalic Acidmentioning
confidence: 99%
“…2022a) (0.1-8%). The regeneration performance of the material was studied for eight cycles (Yang et al, 2022b). Both C (X °C) -SAA and C-SAAoa were applied to a batch of adsorption experiments to determine the performance of this modification.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Although noble metals exhibit good catalytic performance, their high cost and poison susceptibility [ 64 ] limit their potential for large-scale applications and emphasise the demand for alternative, less expensive and readily available high-efficiency catalytic materials. One of the biggest threats to platinum catalytic performance is CO contamination during heterogeneous catalysis.…”
Section: Hydrogen Peroxide Electrochemical Detectionmentioning
confidence: 99%
“…One of the biggest threats to platinum catalytic performance is CO contamination during heterogeneous catalysis. This interference results from the molecular structure of CO, whose triple bond justifies the strong binding capacity on the platinum surface, hindering the analyte from accessing the active catalytic sites available for heterogeneous catalysis [ 64 ]. However, the platinum electrocatalyst’s tolerance to carbon monoxide poisoning can be improved by doping the platinum with other materials such as transition metals [ 65 ], oxides or high-surface-area carbonaceous such as multi-walled carbon nanotubes [ 66 ].…”
Section: Hydrogen Peroxide Electrochemical Detectionmentioning
confidence: 99%
See 1 more Smart Citation